Minimalisasi Biaya Pendistribusian Air PDAM Tirtanadi Cabang Deli Tua dengan Menerapkan Metode Modified Distribution (MODI) - Abimayu, Satria; Dur, Sajaratud; Cipta, Hendra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
PDAM Tirtanadi is a large company owned by Sumatera Utara region which has been operating since 1905. In distributing water, PDAM Tirtanadi spends a lot of money. The purpose of this research is to apply the Modified Distribution (MODI) method in order to achieve minimum costs in distributing water to water companies PDAM Tirtanadi. In completing the transportation method, the researcher uses two stages, namely first to find an initial solution using the North West Corner (NWC) method and secondly to improve the initial solution to find out whether it is optimal or not using the Modified Distribution (MODI) method. The results of the study use the initial solution using the North West Corner method and secondly. improve the initial solution to find out whether it is optimal or not with the Modified Distribution (MODI) method at the water company PDAM Tirtanadi Deli Tua branch in April it was Rp 7,773,282,978